2009
DOI: 10.1177/0091552109348045
|View full text |Cite
|
Sign up to set email alerts
|

Financial Aid and Persistence in Community Colleges: Assessing the Effectiveness of Federal and State Financial Aid Programs in Oklahoma

Abstract: Using a longitudinal, state-wide dataset, this study assessed the effect of financial aid on the persistence of full-time students in associate's degree programs at the Oklahoma community colleges. Three financial-aid sources were examined: the Oklahoma Higher Learning Access Program (OHLAP), Pell grants, and Stafford loans. Results indicate that these forms of financial aid, alone and in combination, were predictors of persistence measured in terms of the student progressing from 1st-year status to 2nd-year s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 36 publications
(55 reference statements)
0
30
0
5
Order By: Relevance
“…John and Starkey 1994), a finding attributed to the host of financial barriers these students face in remaining enrolled and not by recipient of the grant itself. But several studies applying more sophisticated analytic methods have found that Pell Grants had a positive effect on community college student persistence to the 2nd year (Bettinger 2004;Mendoza et al 2009). In either case, our findings support claims that the current availability of need-based grant aid is not sufficient to meet students' total costs of attending community college (Baime and Mullin 2011;Kennamer et al 2010), as approximately two-thirds of the borrowers in our sample belonged to the two lowest income quartiles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…John and Starkey 1994), a finding attributed to the host of financial barriers these students face in remaining enrolled and not by recipient of the grant itself. But several studies applying more sophisticated analytic methods have found that Pell Grants had a positive effect on community college student persistence to the 2nd year (Bettinger 2004;Mendoza et al 2009). In either case, our findings support claims that the current availability of need-based grant aid is not sufficient to meet students' total costs of attending community college (Baime and Mullin 2011;Kennamer et al 2010), as approximately two-thirds of the borrowers in our sample belonged to the two lowest income quartiles.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to prior research that has applied Chen's conceptual model (see Mendoza et al 2009), time in college was captured as a dependent, rather than independent, variable in our study. For the year 3 and year 6 regression models, the cumulative level of federal debt as of year three was added as a predictor variable.…”
Section: Logistic Regressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Hoyt (1999) found that lower level socio-economic students had lower persistence rates. Also, Mendoza, Mendez and Malcolm (2009) confirmed that student who had earned less than $20,000 per year had lower rates of persistence, but students who earned more than $40,000 per year had higher rates of persistence. Contrary to these findings, Conklin (1995) found at one community college that students with a high socio-economic level had lower persistence rates.…”
Section: Socio-economic Statusmentioning
confidence: 73%
“…Subsequently, student persistence has been shown to be positively impacted by receipt of financial aid for students enrolled at the community college (Bettinger, 2004;Cofer & Somers, 2001;Mckinney & Novak, 2013;Mendoza, Mendez, & Malcolm, 2009;).…”
Section: The Impact Of Ses On College Studentsmentioning
confidence: 99%